2006
DOI: 10.1021/ie060844c
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Sonochemical Process Using a Novel Reactor and Taguchi Statistical Experimental Design Methodology

Abstract: The recent increase in the applications of ultrasound for benign environmental remediation, chemical and materials synthesis, and biological processes presents an urgent need to optimize the sonochemical process to reduce the cost of operation and make it economically attractive for large-scale applications. This paper reports for the first time the application of the Taguchi statistical method to design experiments and optimize a sonochemical process. The model reaction chosen for study was the sonochemical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…14 It is noteworthy that the efficiency and even selectivity of sonochemical reactions 15 can be further optimized depending on many experimental parameters (temperature, pressure, acoustic frequency, and intensity), properties of reaction mediums, and even the geometry of reaction vessels. 16 Nevertheless, the sonochemical functionalization carried out here proceeded rapidly in our current basic experimental setup and self-terminated upon formation of a complete monolayer as evident by the constant thickness even after extended (2 h) sonication. In contrast, threedimensional growth of olefins on diamond was observed with extended illumination by using UV photochemical functionalization owing to side reactions 17 induced by the photoemission process.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…14 It is noteworthy that the efficiency and even selectivity of sonochemical reactions 15 can be further optimized depending on many experimental parameters (temperature, pressure, acoustic frequency, and intensity), properties of reaction mediums, and even the geometry of reaction vessels. 16 Nevertheless, the sonochemical functionalization carried out here proceeded rapidly in our current basic experimental setup and self-terminated upon formation of a complete monolayer as evident by the constant thickness even after extended (2 h) sonication. In contrast, threedimensional growth of olefins on diamond was observed with extended illumination by using UV photochemical functionalization owing to side reactions 17 induced by the photoemission process.…”
mentioning
confidence: 88%
“…It took just 1 h to form a self-limiting ideal monolayer thickness on p -type Si(111) which is of the same time frame as the UV photochemical activation method . It is noteworthy that the efficiency and even selectivity of sonochemical reactions can be further optimized depending on many experimental parameters (temperature, pressure, acoustic frequency, and intensity), properties of reaction mediums, and even the geometry of reaction vessels . Nevertheless, the sonochemical functionalization carried out here proceeded rapidly in our current basic experimental setup and self-terminated upon formation of a complete monolayer as evident by the constant thickness even after extended (2 h) sonication.…”
mentioning
confidence: 95%
“…73 Thus, such technologies could make a wet-FGD scrubber more cost-effective and could obviate the need for installation of additional costly control equipment such as an SCR system. We are currently working on process optimization using design of experiment techniques such as response surface and Taguchi statistical methodologies 74,75 to assess the sensitivities of the various experimental parameters and evaluate the effects of other flue gas components, such as SO 2 , O 2 , and CO 2 . The results of these studies will be reported in future publications.…”
Section: Discussionmentioning
confidence: 99%
“…Research efforts on the optimization procedures with a view to arrive at a set of conditions that yields optimal immobilization or adsorption effects and delineates the interaction between the synthesis and process parameters are also important. These should include process optimization of experimental approaches using methodologies such as Taguchi and response surface methods and artificial intelligence (machine learning or neural network) to ascertain new insights under realistic operating conditions and techno-economic analysis. Such studies should help in their cost–benefit evaluations and comparison to available/emerging technologies, aiding progress toward scale-up and industrial applications. These represent knowledge gaps and opportunities to be exploited moving forward.…”
Section: Future Research Needs Challenges and Opportunitiesmentioning
confidence: 99%